A study on the green library practices of selected science high school libraries in Metro Manila - Azul, Michael M.; Silverio, Rochelle S. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2016)
Today, taking care of the environment is one of the most pressed agenda in the world and everyone's contribution towards a more environment friendly society isessential. Libraries are an integral part of society, thus, they are also called for to support this goal.
This study involves seven Science High School libraries from District II and District III of Metro Manila. It focuses on knowing the respondents' institutional and departmental policies on environmental sustainability and their green practices. Additionally, an energy audit is also done to know of the libraries' monthly energy consumption. The data gathered from survey questionnaires and interviews from the Science High School library respondents revealed that: (1) the policies that most of the libraries implement come from their institutions, (2) the most commonly practiced green strategies fall under material conservation area while the least practiced ones are under the library building concerns, (3) the library personnel have a positive view on the implementation of green library practices, and the (4) difficulties that hinder the library staff from implementing green practices include budgetary constraints and lack of manpower. Their energy audits on the other hand showed that the libraries' monthly electricity bills ranges from Php3,992 to Php352.40, depending on the type of equipment that they have and the number of hours they are used.
The study recommends that Science High School libraries should (1) have their own formally written environmental policies. (2) acquire materials on environmental science and promote such, (3) conduct activities which promote environmental awareness, (4) perform conscious efforts of applying greening strategies,and, (5) libraries in knowing green schools be studied as well.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: High school Libraries -- Philippines -- Manila Metropolitan Area; Sustainable development -- Philippines -- Manila Metropolitan Area